Perkembangan Kristologi dari Abad Pertama hingga kelima: Sebuah Kajian Historis dan Teologis (International Forum of Researchers and Lecturers, 2025)
The development of Christology in the first century, from up to the 5th century, shows how the Church formulated the true teachings of Jesus Christ on different theological agendas in the middle. This struggle not only strengthened the understanding of Christ's identity, but also served as a basis for Christian faith in understanding the operation of salvation. This research is a qualitative research using the literature study method. The research was designed to analyze the development of Christology from the first century to the fifth century, especially in understanding how theological thinking about Jesus Christ developed in church history.